Sintering behavior and dielectric properties of Al 2O 3 ceramics with CaMgSi 2O 6 addition - Wang, H.; Feng, S.; Yang, W.; Ma, H.; Jia, Guohua; Xu, S. (2012)
Al 2O 3CaMgSi 2O 6 ceramics with different amount of CaMgSi 2O 6 additions were prepared by a conventional solid-state method, and the effects of CaMgSi 2O 6 addition on the sintering behavior and dielectric properties of Al 2O 3 ceramics have been investigated. CaMgSi 2O 6 was used as a liquid sintering aid to effectively lower the sintering temperature of Al 2O 3 ceramics and its addition resulted in the presence of CaAl 2Si 2O 8 and MgAl 2O 4 phases. However, the CaMgSi 2O 6 addition deteriorated the dielectric properties of Al 2O 3CaMgSi 2O 6 ceramics because of the higher dielectric loss of the derived CaAl 2Si 2O 8 and MgAl 2O 4 compared with that of Al 2O 3 ceramics. After sintered at 1450°C, the Al 2O 3CaMgSi 2O 6 ceramic with 10 wt% CaMgSi 2O 6 addition possessed dielectric properties of e r = 9.83, tan d = 1.5 × 10 -4 (1 MHz) and Q × f = 20,425GHz (f 0 = 12 GHz). © 2012 The Ceramic Society of Japan.